The Role of Personality, Adversity Intelligence and Creativity in Increasing Entrepreneurial Interest Through Student Involvement in Entrepreneurship Lectures - Setyaji, Bayu; Yanto, Heri; Prihandono, Dorojatun (Universitas Negeri Semarang, 2020)
Entrepreneurial interest does not grow by itself but can influence by several factors. The purpose of this study is to examine the relationship between determinants in entrepreneurial interests, namely personality, adversity intelligence, creativity and student involvement. This research uses a quantitative approach and path analysis. From the sample of 168 students, it found that the personality, adversity intelligence and creativity of each affected the involvement of students. Then the personality, involvement of students and creativity each affect the entrepreneurial interest. All variables in this study are in the high criteria in descriptive analysis. The results of the research may be to consider in conducting policies by related parties.